Public health and economic impact of 13-valent pneumococcal conjugate vaccine in US adults aged ≥50 years - Weycker, Derek; Sato, Reiko; Strutton, David; Edelsberg, John; Atwood, Mark; Jackson, Lisa A (Vaccine, 2012)
Highlights ► We modeled the impact of vaccination on risk of pneumococcal disease in older US adults. ► Model projections suggest that use of PCV13 (vs. PPSV23): (i) without revaccination, would reduce cases of disease and lower total costs; and (ii) with revaccination every 5–10 years, would result in the fewest cases and lowest costs. ► Projected impact of PCV13 in older US adults is favorable vs. current practice.